Risk Factors of Pulmonary Tuberculosis in Type 2 Diabetes Mellitus in Yogyakarta - Fatma Nuraisyah; Ningsih Juliana; Dana Astaria; Noor Khalisah; Dzikrina Miftahul Fitri Al Fatih; Syamsumin Kurnia Dewi; Sunarti; Triyani Marwati (Journal of Epidemiology and Public Health, 2024)
Background: The prevalence of pulmonary tuberculosis (TB) increases along with the increasing prevalence of Type 2 Diabetes Mellitus (T2DM) patients. The frequency of TB in type 2 DM patients (10 to 15%) and the prevalence of this infectious disease is 2 to 5 times higher in DM patients compared to non-diabetics. This study aimed to analyze the risk factors for pulmonary TB in T2DM patients in Yogyakarta.Subjects and Method: This study uses a case-control study design conducted at RESPIRA Lung Hospital Yogyakarta from January 16 to February 20, 2023. The number of samples was 52 people with a total of 26 people in the case and control groups. Samples were taken by consecutive sampling technique. The independent variables were age, gender, employment, education, BMI, smoking status, clinical symptoms, family history of TB, previous history of TB, and income level). The dependent variable is the incidence of TB in DM patients. Control groups are respondents without a diagnosis of DM and TB patients. Conversely, the cases are personal with diagnosis TB and DM patient Data were collected using a questionnaire. Data analysis was carried out descriptively, bivariate with Chi-square, and multivariate with multiple logistic regression.Results: The demonstrated research that the risk factors that influence the incidence of TB in T2DM patients are gender (aOR = 9.60; 95% CI: 0.14 to 55.96; p=0.012), Age (aOR=0.24; 95% CI: 0.07 to 0.76; p=0.015).Conclusion: The female sex has a 9.60 times higher risk of experiencing TB compared to men in T2DM patients.